Turkey in MENA, MENA in Turkey: Reasons for popularity, limits of influence - Sinem Adar (Stiftung Wissenschaft und Politik (SWP), 2024)
Turkey's popularity in the MENA region has increased since the AKP's rise to power in 2002. People-to-people contacts, economic progress, and a perceived European lifestyle have contributed to Turkey's popularity in the MENA region. Turkey's seemingly competitive political system and strong participation in elections are sources of appreciation. However, the meanings attributed to the Turkish political system have changed over time. Ankara's confrontational rhetoric on the perceived double standards of Western states and its calls for reform of the international system are welcomed. Turkey's increased popularity does not easily translate into broad regional influence. Ankara's credibility has deteriorated in the eyes of the region's elites. Its support of Sunni Islamists in the of the Arab uprisings antagonised the region's autocratic elites, ushering in a period of isolation between 2013 and 2020. Turkey's recent efforts to reintegrate in the region have thawed relations with Egypt, Saudi Arabia and the UAE, but incurred reputational costs vis-à-vis Sunni Islamists. Authoritarian practices and rising xenophobia against Syrian refugees and other Arab citizens also constrain Turkey's influence in the region.
Keywords: 320; Turkey; MENA region; United States; European Union; NATO; Justice and Development Party (AKP); Recep Tayyip Erdoægan